City of the many - Max Ott; Norbert Kling; Christian Zöhrer (Urban Transcripts, 2020)
The city of Munich has recently held an ideas competition for a 600 hectare site in the northeast of the municipality, which is characterised by a mix of suburban housing, agricultural uses and horse riding facilities. The task was to develop three scenarios for its future development, comprising commercial and residential uses together with public infrastructure. The competition brief was limited to delivering fixed master plans while important questions regarding land policy and long-term planning processes were left out. However, if we understand the city as a common good, such fundamental questions must not be neglected. Therefore, we have sketched out a path towards a production of urban spaces that shall be accessible for as many people as possible.